PENGARUH MODEL PEMBELAJARAN COURSE REVIEW HORAY (CRH) MENGGUNAKAN ALAT PERAGA TERHADAP PEMAHAMAN KONSEP MATEMATIS - Putri Yolanda; Yohanes; Awatif (Hira Institute, 2025)
This study aims to describe that the understanding of mathematical concepts using the Course Review Horay (CRH) learning model using teaching aids is better than conventional learning. This study uses an experimental method with a population of all students of class VIII of SMP N 1 Merangin in the 2023/2024 academic year consisting of 8 classes and totaling 209 people. The selected sample was class VIII A as the experimental class and VIII D as the control class. The analysis technique used to test the hypothesis is the z-test because the data is normally distributed and the variance is not homogeneous. Based on the analysis of the final test in the experimental class, an average of 44.37 was obtained, while in the control class an average of 33.19 was obtained. The results of the hypothesis test were obtained using a linear regression test, the value of Y = 6.970 + 0.412x was obtained. In the calculation of the significant test, the calculated f value = 22.316 and f table with a significance level of 0.05 because the two-tailed test then df (N1) = 1 and df (N2) = 51 then F table = 4.03. Based on the calculation results, it was obtained that the calculated f value> F table, namely 22.316> 4.03, then H0 was rejected, which means that there is a significant influence between students' understanding of mathematical concepts using the Course Review Horay (CRH) learning model using teaching aids in class VIII students of SMPN 1 Merangin in the 2023/2024 academic year.